The Relationship Between Physical Activity Levels and Physical Fitness in Students at Junior High School 2 Ciwidey - Dafid Ryansyah Wiluya; Surdiniaty Ugelta; Adang Suherman (Universitas Negeri Semarang, 2026)
Physical activity is a key determinant of physical fitness and plays an essential role in supporting health and functional capacity among adolescents. This study aimed to examine the relationship between physical activity levels and physical fitness among students of Junior High School 2 Ciwidey. A quantitative correlational study with a cross-sectional design was conducted involving 90 eighth-grade students selected using cluster sampling. Physical activity levels were measured using the International Physical Activity Questionnaire–Short Form (IPAQ-SF), while physical fitness was assessed through the Multistage Fitness Test (MFT) to estimate maximal oxygen uptake (VO₂max). Descriptive analysis was used to describe physical activity and fitness profiles, while the Spearman rank correlation test was applied due to non-normal data distribution. The results showed that most students were categorized as having moderate physical activity levels (52%), followed by low (33%) and high (11%) activity levels. Physical fitness assessment revealed that male students generally demonstrated higher VO₂max levels compared to female students, who were predominantly classified in the very low and low categories. Correlation analysis indicated a significant positive relationship between physical activity and physical fitness (r = 0.217; p = 0.040), although the strength of the relationship was weak. These findings suggest that higher physical activity levels are associated with better cardiorespiratory fitness among junior high school students. Therefore, efforts to increase the frequency and intensity of physical activity through school-based programs and supportive environments are necessary to improve students’ physical fitness and overall health.